THE APPLICATION OF SOLAR INSTALLATIONS IN AIR CONDITIONING SYSTEMS OF BUILDINGS BASED ON EVAPORATIVE COOLING OF AIR - Ismailova , Zumrad; Anarbaev , Anvar (UZBEKISTAN — 2030: PROSPECTS FOR INNOVATION, SCIENCE AND EDUCATION, 2025)
The possibility of using solar installations in air conditioning systems for buildings has been considered. This allows for a reduction in the temperature level of the cold produced by increasing the efficiency of latent heat assimilation in the conditioned spaces. The text also demonstrates ways to reduce energy consumption through the targeted combination of various flow exchange schemes. Schemes for the rational use of phase change heat and the renewable energy resource of thermodynamic non-equilibrium of atmospheric air are presented